THE EFFECT OF JOB SATISFACTION ON THE PRODUCTIVITY OF GENERATION Z EMPLOYEES IN THE PRODUCTION DIVISION OF PT TAEKWANG INDUSTRIAL INDONESIA - Putri, Revita Maulida; Sopiawadi, Mutqi (STIESA Press, 2026)
In the era of globalization and intense industrial competition, human resources are a key factor in organizational success. PT Taekwang Industrial Indonesia, Subang, has experienced a decline in employees from over 40,000 to 27,375 in 2023 and a high turnover rate of young workers (18.7%). This highlights the urgency of examining job satisfaction as a determinant of Generation Z employees’ productivity. This study applied a quantitative descriptive-verificative design with 35 Generation Z respondents from the Production Division. Data were collected using a Likert-scale questionnaire (8 items for job satisfaction and 5 items for productivity) and analyzed through validity and reliability tests, classical assumption tests, simple linear regression, and t-tests using SPSS 25. The results indicate that job satisfaction has a positive and significant effect on productivity. The coefficient of determination (R²) of 0.332 shows that job satisfaction contributes 33.2% to employee productivity, while 66.8% is influenced by other factors. Thus, the higher the job satisfaction, the higher the productivity achieved. The implication of this study emphasizes the need for the company to strengthen aspects of job satisfaction such as compensation, work environment, and career opportunities to reduce turnover and increase productivity.